Improving desliming: the use of rheology and surface chemistry interactions - Francisco J. Sotillo (Instituto de Ingenieros de Minas del Peru, 2003)
"The paper point out the fundamentals of surface chemistry used on the design of this organic polymer, and its effect on the rheology of clayishphosphatic slurries in comparison with other available dispersants. Reducingthe viscosity of clayish slurries increases phosphate particles settling rates, and decreases value losses during desliming using gravitational forces. Also presented the improvement of desliming using centrifugal forces by achieving better separation of the ore from the slimes during cycloning."